Hepatic CEACAM1 Over-Expression Protects Against Diet-Induced Fibrosis and Inflammation in White Adipose Tissue - Lester, Sumona G.; Russo, Lucia; Ghanem, Simona S.; Khuder, Saja S.; DeAngelis, Anthony M.; Esakov, Emily L.; Bowman, Thomas A.; Heinrich, Garrett; Al-Share, Qusai Y.; McInerney, Marcia F.; Philbrick, William M.; Najjar, Sonia M. (Frontiers in Endocrinology, 2015)
CEACAM1 promotes insulin extraction, an event that occurs mainly in liver. Phenocopying global Ceacam1 null mice (Cc1–/–), C57/BL6J mice fed a high-fat diet exhibited reduced hepatic CEACAM1 levels and impaired insulin clearance, followed by hyperinsulinemia, insulin resistance and visceral obesity. Conversely, forced liver-specific expression of CEACAM1 protected insulin sensitivity and energy expenditure, and limited gain in total fat mass by high-fat diet in L-CC1 mice. Because CEACAM1 protein is barely detectable in white adipose tissue, we herein investigated whether hepatic CEACAM1-dependent insulin clearance pathways regulate adipose tissue biology in response to dietary fat. While high-fat diet caused a similar body weight gain in L-CC1, this effect was delayed and less intense relative to wild-type mice. Histological examination revealed less expansion of adipocytes in L-CC1 than wild-type by high-fat intake. Immunofluorescence analysis demonstrated a more limited recruitment of crown-like structures and qRT-PCR analysis showed no significant rise in TNFα mRNA levels in response to high-fat intake in L-CC1 than wild-type mice. Unlike wild-type, high-fat diet did not activate TGF-β in white adipose tissue of L-CC1 mice, as assessed by Western analysis of Smad2/3 phosphorylation. Consistently, high-fat diet caused relatively less collagen deposition in L-CC1 than wild-type mice, as shown by Trichome staining. Coupled with reduced lipid redistribution from liver to visceral fat, lower inflammation and fibrosis could contribute to protected energy expenditure against high-fat diet in L-CC1 mice. The data underscore the important role of hepatic insulin clearance in the regulation of adipose tissue inflammation and fibrosis.